Three new earthworms of the Amynthas corticis-group (Clitellata: Megascolecidae) from the Nam Et-Phouleoi, Laos - Hong, Yong; Inkhavilay, Khamla; James, Samuel W. (Zootaxa, 2024)
Three new earthworms of the Amynthas corticis-group (Clitellata: Megascolecidae) from Phouleoi Mountain, Lao PDR. Earthworm specimens were collected from Mt. Phouleoi, Viengthong District, Houaphanh Province, Lao PDR. The species belong to the pheretimoid earthworms. All three holandric species key out to the A. corticis-group in Sims & Easton (1972), having spermathecal pores in 5/6–8/9. The new species are: Amynthas ammalinei sp. nov., Amynthas xayi sp. nov., and Amynthas piyakarnae sp. nov. Amynthas ammalinei sp. nov. has male pores superficial on small round porophores, 0.16–0.31 circumference apart. Amynthas xayi sp. nov. has male pores superficial in XVIII at centers of round porophores, 0.17–0.29 circumference apart. Amynthas piyakarnae sp. nov. has male pores superficial on transverse elevated elongate oval pads equatorial on XVIII, pads surrounded by 3–4 small outer rings, 0.25–0.31 circumference apart.